Pengembangan LKPD Project Based Learning Pembelajaran IPAS Kelas IV SD Negeri 40 Pontianak Utara - Lauren, Novia; Kartono, Kartono; Salimi, Asmayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This research generally aims to develop and produce student worksheet teaching material (SWTM) that are valid, interesting, and effective to be used to support the learning of SD Negeri 40 North Pontianak fourth grade student. This research use the method of research and development (RND) with the approach of mixed borg and gall method, that contain the ten steps of research and that is information gathering, planning, prototype developing, early testing , product revision, field testing, field testing revision, operational field testing, final product revision , deployment and implementation. At the product testing stage done at SD negeri 40 north Pontianak fourth grade with the amount of 20 student, the result of this research is a project based learning the IPAS learning material